The emergent terrains of 'higher education regionalism': how and why higher education is an interesting case for comparative regionalism. Issue 3 (2nd July 2016) - Chou, Meng-Hsuan; Ravinet, Pauline
ABSTRACT: The introduction of regional political initiatives in the higher education sector symbolizes one of the many aspects of the changing global higher education landscape. Remarkably, these processes have generally escaped comparative scrutiny by scholars researching higher education policy cooperation or regional integration. In this article, we demonstrate how and why higher education policy cooperation is an interesting case to study through the lens of comparative regionalism. To do so, we describe the emerging debate on comparative regionalism in EU studies. We explain what has led to this call to broaden analytical perspectives in examining regional integration and how it may be useful for scholars working in the higher education field to engage with this new research direction. In setting out this research agenda, we also spotlight the difficulties in operationalizing comparative regionalism for higher education studies and suggest ways forward.